Comparative evaluation of etch pattern, the length of resin tags, and shear bond strength of all-in-one adhesive system on intact enamel with and without phosphoric acid pre-etching: An in vitro investigation - Savitha Adiga; Ida Ataide; Marina Fernades (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study is to compare the etch pattern, resin tag length and the shear bond strength (SBS) of all-in-one adhesive system (Clearfil S 3 bond) on intact enamel with and without phosphoric acid (PA) preetching. Materials and Methods: Freshly extracted 80 caries free cleaned sectioned crowns of upper permanent central and lateral incisors were mounted on acrylic blocks. The samples were divided into four Groups (A, B, C and D). In Group A and B the application of self-etch adhesive (SEA) was carried out without prior etching with PA and light curing performed (n = 20). In Group C and D etching was carried out with 37% PA before the application of SEA and light curing was carried out. The etch pattern, resin tag length were analyzed using scanning electron microscope and the SBS was analyzed using Instron Universal testing machine. Statistical Analysis Used: Data were analyzed with Mann-Whitney U-test using Statistical Package for Social Science version 11.5 Software. Results: The statistical analysis revealed that there was significant increase in the depth of penetration of resin tags and in the SBS of composite in Group C and D where PA pre-etching carried out in unground enamel than Group A and B (P < 0.05%). Conclusion: The results indicate that out of both treatment groups, pre-etching the intact enamel with 37% PA resulted in deeper etch pattern, formation of longer resin tags and increased SBS of the Clearfil S 3 bond to unground enamel.